Compositional analysis of natural pomegranate peel powder dried by different methods and nutritional and sensory evaluation of cookies fortified with pomegranate peel powder - Muhammad, Ali; Dayisoylu, Kenan Sinan; Pei, Jinjin; Khan, Muhammad Rafiullah; Salman, Muhammad; Ahmad, Rafiq; Ullah, Hakim; Noor, Gul Rah (Frontiers in Nutrition, 2023)
Introduction: Fortification of cereal products with natural plant extract is an interesting approach to fulfill the dietary requirement of the people. Methods: Peels of pomegranate (rich source of natural compounds) were cut into small pieces and dried in three different methods such as sun drying (SUD), solar drying (SOD), and oven drying (OD) and sun drying (SUD). The fine powder was prepared and proximate compositions (protein, ash, moisture, fats, fiber, and carbohydrates), minerals (zinc, iron, calcium, and potassium), total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity (DPPH) of the pomegranate peel powder (PP) were evaluated. Fine wheat flour (FWF) was fortified with different concentrations (3, 6, 8, 10 and 12g) of PP powder, cookies were prepared and all the above analysis along with physical parameters (weight, width, thickness, spread ration) and sensory analysis were conducted. Cookies without PP powder were served as control. Results and Discussion: Results showed that a solar methodSOD was the best for drying the PP powder in terms of compositional analysis. Addition of PP powder significantly (P<0.05) enhanced the nutritional value, minerals profile and physical attributes of the fortified cookies. Sensory analysis of fortified cookies indicated that the cookies were acceptable to the sensory panel. Therefore, in conclusion, PP powder dried by SOD method could be used commercially in baking industries to provide nutritional enriched cookies to fulfill the dietary requirements of the people.